Contribuições de um projeto de formação on-line para o desenvolvimento profissional de professoras do 1º ano do ensino fundamental - Rodrigues, Marilce da Costa Campos (2013)
In this investigation, the aim is to analyse the contributions and limits of a continuous online training project for the professional development of teachers of the 1st year of basic education. The research question is: What are the limits and contributions of an online teacher-training course in the professional development of teachers? This development is related to the learning and teaching processes and of being a professional teacher, and acts as a knowledge basis for teaching. The methodological reference adopted is supported by a constructive-collaborative interaction model between teachers and researchers and focusses on the construction of investigation strategies and the promotion of professional development processes for teachers. The training strategies used were carried out in distance mode through the digital learning environment of the Teachers portal of the UFSCar. The course, with a total of 120 hours and focussing on teaching the initial years of primary education, was developed in the period between Sept. 2010 and May 2011. It was based on the understanding that professional teacher development takes place throughout their careers and continuous teacher training can contribute to this process. Its contributions and limitations are being investigated through the eyes of the teachers, that is, we take into account what they told us in the different data collection instruments and at different points of the training process. Our interpretations are based on the learning, the difficulties and the teacher knowledge required to teach the 1st year of primary education. The narratives constructed during the interventions by three experienced teachers represent the data interpreted in the study. Other instruments used in this process are: reflective memorials, training reports, teaching cases, reflective journals, a forum, individual summaries on a reference framework on the student knowledge base, and an initial questionnaire. As a result of the investigation, it was found that there was a contribution to professional teacher development in the following aspects: the training content contextualized to the teaching work carried out in the initial years; the feedback on what the participating group`s investigation found; sharing experiences on literacy with teachers from different Brazilian states; the possibility of reviewing the inherent role when teaching the 1st year of basic education; the discussion of the knowledge that composes the teaching basis; the specifics of the teaching content; the overall pedagogy and the pedagogical content. The limits are related to the difficulties in obtaining effective participation from all the teachers and the challenges presented by the dynamic and flexible digital learning environments used to create a collaborative network.